Status Kelengkapan Imunisasi Difteri Pada Kejadian Difteri Di Wilayah Surabaya - Diyah Arini; Shofia Kulsum; Ayu Citra Mayasari (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
One of the diseases of Extraordinary Events in East Java Province is diphtheria disease. Diphtheria is an acute infectious disease of the upper respiratory tract in the system caused by the bacterium Corynebacterium Diphtheria. One of the factors that may affect the incidence of diphtheria is an incomplete immunization status. The purpose of this research is to analyze the relationship status of the completeness of immunization with diphtheria incidence in the region of Surabaya. Design research Analytic approach with Cross-Sectional Correlation. The independent variable complete immunization status of diphtheria and dependent variable is diphtheria occurrence.  The population of the research was as many as 29 people who suffered from diphtheria in 2017 and sample as many as 27 people who suffered from diphtheria in 2017in the city of Surabaya. Using a technique Simple Random sampling. The instruments of research using questionnaires, observation secondary data: laboratory results and sheet book KMSfor incomplete immunization status data and diphtheria incidence, tested use the spearman rho correlation. Statistical results with Spearman Rho Correlations test obtained ρ = 0.03 with ρ ≤ 0.05. It states that H0 is rejected H1 accepted as well as the result of correlation coefficient – 0.411. This shows the existence of the relationship between complete immunization status of diphtheria with diphtheria occurrence in the region of Surabaya. The implications of this research show that the diphtheria immunization incompleteness affects the incidence of diphtheria. Expected health workers can better do health promotion about the importance of immunization and prevention of diphtheria transmission, registration, and grant of immunization in the community.Keywords: Diphtheria, Immunization, Surabaya